(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
Indian’s long-standing identity as a secular democracy is increasingly being contested by ascendance of far-right ideological narratives, particularly those associated with the concept of “Hindutva”. With the electoral prominence of the Bharatiya Janata Party (BJP) and ideological influence of the Rashtriya Swayamsevak Sangh (RSS), ‘Hindutva’ has emerged as a dominant political discourse. The ideology envisions India as a fundamentally Hindu nation, wherein citizenship and national belonging are closely tied to Hindu cultural affiliation. In this framework, non-Hindu communities are expected either to conform to majoritarian norms or accept subordinate status. Political actors and affiliated organizations have strategically utilized mass media and discursive tools to foster communal polarization, often targeting Muslim and other minority communities. This has contributed to increased marginalization, socio-political exclusion, and incidents of communal violence. Moreover, such narratives have extended beyond national borders, contributing to the dissemination of exclusionary rhetoric within the South Asian region. Anti-Muslim sentiment promoted by certain Hindu nationalist factions has exacerbated regional tensions and reinforced militarized and nationalistic postures. There is a growing concern that Hindutva-aligned narratives may influence minority Hindu populations in neighboring countries, potentially catalyzing reactive mobilizations among other religious groups, including Muslim and Buddhist factions. This discursive spill over heightens the risk of reciprocal extremism, deteriorates inter-state relations, and intensifies communal tensions. Consequently, these dynamics pose a substantive threat to regional stability and minority rights across South Asia.